WRITING ASSESSMENT: STUDENTS‟ RESPONSE AND INSTRUCTORS‟ RESPONSE TOWARDS FORMATIVE & SUMMATIVE ASSESSMENT. - Adilah, Farah; Nursyuhada, .; Rozienna., Nur; Hasnah, .; Hulwani., Zati (PEOPLE: International Journal of Social Sciences, 2016)
In education, assessment is an important reporting instrument for students’ performance. It gives a strong implication on students learning. According to Gibbs &Simpson (2003), assessment can influence students learning, either in a good or bad way. They highlighted five conditions which assessment can either support or obstruct students learning. The five conditions are; quantity and distribution of student effort, quality and level of students’ effort, quantity and timing of feedback, quality of feedback, and students’ response to feedback. This study is conducted as an effort to identify students’ and instructors’ responses towards writing assessments in English for Academic Purposes (EAP) course. Identifying the responses of students and instructors towards assessment is crucial as it can analyse how well the writing assessment in the course is supporting the students’ learning. A survey using the Assessment Experience Questionnaire (AEQ) has been administered to 185 students. Besides, Interviews were conducted with the instructors of the EAP course to identify their response. The finding of this study is hopefully will assist learning institution in improving the language assessment strategies especially in ensuring how the assessments can support students learning.